Recursos hídricos subterrâneos e estratégias de produção agropecuária no semiárido brasileiro - Nunes, Kenya Gonçalves (2021)
Groundwater can be an excellent alternative resource for irrigation, especially in conditions of water shortage, which is recurrent in the Brazilian Northeast. However, it must be considered that the exploitation of groundwater resources without the proper characterization of water reserves jeopardizes the maintenance of the quantity and quality of water available. The characterization of the water reserves is fundamental for the water management of hydrogeological units of alluvial in semi-arid regions, in view of the strategic water condition of the alluvial in a scenario of constant water shortage. The research aimed, in general, to quantitatively and qualitatively characterize water reserves, in alluvial aquifer under semi-arid conditions and in strategic stretches of the state of Ceará, which use well water for agricultural activities, and to obtain information to guide the management of irrigation, with a view to increase the water productivity. Specifically, it had the following objectives: 1. to characterize the groundwater reserves in the Morada Nova Irrigation Scheme; 2. to analyze the quality of the groundwater in the Morada Nova Irrigation Scheme; 3. to establish a field experiment to achieve ideal levels of the combination of production factors water, organic manure and soil cover in Vale do Curu region. From the registration of the wells it was carried out the hydraulic characterization, through the variability of static levels, the determination of the operation flow, the specific capacity, the hydraulic conductivity, the transmissivity, the effective porosity and the radius of influence. These results allowed the determination of the renewable, permanent and exploitable reserves. For the evaluation of the quality of the water of the wells, the samples were collected in the dry season, with the objective of determining the quality of the water for irrigation purposes and the heavy metals concentration in the most critical condition, and also coincident with the period of irrigated crops. The experimental unit was irrigated with a localized system and water from a shallow well, with the purpose of achieving the best combination of levels of production factors. The results confirm the importance of groundwater reserves for the continuous production of agricultural activities. However, they also highlight the necessity of information and strategies of water management of the available resources in order to guarantee water sustainability. The quality of groundwater, in general, is not a limiting factor for its use. Finally, the use of soil and water conservation practices can enhance the use of groundwater resources.